Mengidentifikasi Isu-isu Pendidikan di Indonesia dan Solusinya - Sukari, Sukari; Sugiyarti, Sri (TSAQOFAH, 2024)
This paper presents the challenges faced by the education system in Indonesia along with potential solutions. The aim of this paper is to discuss and elaborate on the educational issues that pose challenges to Indonesia’s education system and to provide effective solutions for improving the system to make it more inclusive, of higher quality, and aligned with societal needs and contemporary developments. The research method employed in this study is a literature review. The findings indicate that Indonesia’s education system faces several key challenges, including unequal access to education between urban and rural areas, variations in teaching quality, curriculum relevance to labor market needs, teacher welfare, and the management of education funding. Educational funding must be managed more efficiently and transparently to ensure equitable budget allocation and optimal use of resources.